(3GdJShjb GdOhdj (B(marketing international)s - (3gfGA(B, (3Yajas ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2022)
(3jJfGhd gPG GdcJGH eaGgje eJYdbI HGdJShjb GdOhdj, MjK Je GdJYQV ajg Edi eaghe hJWhQ fTGWg, JhVjM GdaQhbGJ eG Hjf GdJShjb GdOhdj hGdJShjb GdeMdj, ceG Je GdJWQb ajg Edi GdeHGOF hGdCSS, hUa Cge GdYbHGJ Gdeecf ehGLgJgG aj GdJShjb GdOhdj, HMhK GdJShjb GdOhdj, fXGe eYdheGJ GdJShjb GdOhdj, djJe JMdjd HjFg HTcd cGed, eY Jbjje GdCShGb GdOhdjI hfeW GdONhd EdjgG(B.s
(3eQGLY U(B.105 s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJShjb GdOhdjs